A study of histocompatibility antigens in patients with motor neuron disease in the northern region of England. Issue 4 (April 1986) - Woo, E; Nightingale, S; Dick, D J; Walls, T J; French, J M; Bates, D
Abstract : Histocompatibility antigen (HLA A, B and DR) serotyping was performed on 65 patients with motor neuron disease in the northern region of England and compared to a large control population from the Newcastle upon Tyne area. Thirty two patients had amyotrophic lateral sclerosis, 17 had progressive bulbar palsy and 16 had progressive muscular atrophy. Ten patients had a more slowly progressive course. No significant HLA associations were observed in the motor neuron disease patients. Subdivision of the patients by the clinical course of their disease did not reveal any significant associations. Forty six motor neuron disease patients from the Newcastle upon Tyne area had a reduced frequency of HLA DR4 compared to the local control population. The relevance of histocompatibility antigens to the pathogenesis of motor neuron disease is discussed.